47.4k views
1 vote
HELP
PLEASE.
Simplify the expression.
x^2+2x-24/x^2-x-42

HELP PLEASE. Simplify the expression. x^2+2x-24/x^2-x-42-example-1

2 Answers

7 votes

Answer:

Explanation:

x² + 2x - 24 = x² + 6x - 4x - 4 * 6

= x(x + 6) - 4(x + 6)

= (x + 6) (x - 4)

x² - x - 42 = x² -7x + 6x - 6 * 7

= x(x - 7) + 6(x - 7)

= (x - 7) (x + 6)


(x^(2)+2x-24)/(x^(2)-x-42)=((x + 6)*(x-4))/((x+6)(x-7))\\\\\\=(x-4)/(x-7)

User XOR
by
5.0k points
4 votes

Answer:


(x - 4)/(x - 7)

Explanation:


\frac{ {x}^(2) + 2x - 24 }{ {x}^(2) - x - 42 } \\ ((x + 6) (x - 4))/((x - 7)(x + 6)) \:the \: term \: will \: be \: simplified (x + 6) \\ and \: we \: will \: be \: left \: with \: (x - 4)/(x - 7)

User Yatanadam
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.